Metabolic syndrome predicts long-term mortality in subjects without established diabetes mellitus in asymptomatic Korean population: A propensity score matching analysis from the Korea Initiatives on Coronary Artery Calcification (KOICA) registry. Issue 49 (December 2016) - Won, Ki-Bum; Chang, Hyuk-Jae; Han, Donghee; Sung, Jidong; Choi, Su-Yeon
Abstract : Abstract: Despite the different features of diabetes mellitus (DM) in Asian populations compared with Western populations, the impact of metabolic syndrome (MetS) on long-term mortality according to DM status has not yet been elucidated in the Asian population. After performing 1:1 propensity score matching (PSM) using clinical variables including age, gender, smoking, and individual MetS components between DM and non-DM subjects from the data of the Korea Initiatives on Coronary Artery Calcification registry, mortality was evaluated according to DM and MetS in 14, 956 asymptomatic Korean subjects. The mean follow-up duration was 53.1 months (interquartile range: 33–80). The overall prevalence of MetS was 60%. DM subjects had higher mortality compared with non-DM subjects (1.2% vs 0.7%, respectively; P = 0.001); the cumulative mortality by Kaplan–Meier analysis was higher in DM subjects than in non-DM subjects (log-rank P = 0.001). DM increased the risk of mortality in PSM participants (hazard ratio [HR] 1.74; P = 0.001). In non-DM subjects, MetS (HR 2.32) and one of its components, central obesity (HR 1.97), were associated with an increased risk of mortality (both P < 0.05). In contrast, there was no significant difference in the risk of mortality according to MetS or its components in DM subjects. After adjusting for confounding risk factors, it was shown that MetS independently increased the risk of mortality in non-DM subjects. Compared with non-DM subjects, DM subjects have an increased risk of long-term mortality among PSM participants. MetS appears to have an independent impact on mortality in subjects without established DM among the asymptomatic Korean population. Our results may not be applicable to the whole subjects with MetS because the PSM using MetS components was performed between subjects with and without DM which was very high risk for adverse clinical events. Abstract : Supplemental Digital Content is available in the text